Market segmentation for peppers and tomatoes in Eastern and Western Africa - Ambali, Mwasilwa; Zohoungbogbo, Herbaud; Ayenan, Mathieu; Kaki, Rodrigue; Eybishitz, Assaf; Barchenger, Derek; Schreinemachers, Pepijn (CGIAR System Organization, 2024)
The agriculture sector is facing a critical gap in data regarding the future preferences and requirements of key stakeholders such as farmers, processors, and consumers, particularly in the context of public sector vegetable breeding research. While the CGIAR mandates crops benefit from the Seed Product Market Segment (SPMS) database, vegetables are notably absent, despite their significance for nutrition, health, income, and biodiversity. This poster explains the process used to determine market segments and target product profiles for tomatoes and peppers in Africa through workshops and research conducted by WorldVeg in collaboration with the CGIAR Initiative on Market Intelligence. WorldVeg, which develops both finished and nearly-finished breeding lines, conducted a market segmentation exercise for tomatoes and peppers in Africa. The exercise was based on the 8 market segmentation criterion with necessary customizations to address the unique characteristics of each vegetable crop. For East and West Africa the study found 16 tomato segments. The findings indicate that tomato production in Western and Eastern Africa is distinguished by altitude, with Western Africa only on lowland cultivation below 300 meters and Eastern Africa on highland cultivation above 300 meters, necessitating region-specific disease resistance traits. For hot peppers in East and West Africa 15 different segments were found. It appears that Western Africa prefers habanero peppers, while Eastern Africa's market is diverse, with chili peppers being the primary crop and varying market segments across countries. The market segmentation for tomatoes and peppers provides a foundational understanding of market requirements.